(untitled) (Journal of Economic Research & Business Administration, 2018)
Job creation is one of the important stages in eliminating poverty in the world, and in this direction the most successful and competitive institution is social entrepreneurship. Defining the essence of social entrepreneurship, we can say that social entrepreneurship is an activity aimed at solving social problems by finding new or additional resources and a new way of applying them through the synergy of the opportunities of society, business and the state, the synergy of social and entrepreneurial activity. Social entrepreneurship connects the social purpose of the organization with entrepreneurial innovation and the achievement of sustainable self-sufficiency. Social entrepreneurship is an institutionally mature form of intersectoral partnership in which the state, business and non-profit organizations find ways of cooperating to solve social problems. In Kazakhstan, this is a fairly young phenomenon, but there is already a successful practice. At the same time, at this stage, the degree of scientific elaboration of the problems of the development of social entrepreneurship in Kazakhstan lags far behind the practice. Therefore, in general, there is a simplified representation and misunderstanding of the nature of social entrepreneurship on the part of the state and business, the difficulties of legislative and administrative promotion of the idea.